Praksa ocenjevanja znanja pri tujem jeziku stroke v slovenskem visokošolskem prostoru - Svetlin Gvardjančič, Polona (Vestnik za tuje jezike, 2018)
In recent decades, interest in assessment has increased in relation to both tertiary education and languages for specific purposes (LSP). The theoretical part of this paper elucidates the reasons for this shift and draws attention to key topics of interest to researchers in this field. A study was conducted to determine current practice in LSP assessment at Slovenian higher-education institutions. Its findings confirm the central role of LSP teachers in all the tasks relating to grading students' proficiency: selecting the assessments methods, preparing tests, and assigning grades. Assessment practice indicates that teachers carefully include topics relevant to the individual discipline for the languages they teach and, as far as actual assessment is concerned, they follow current trends in education, which is reflected in the use of various forms of assessment. Even though they feel it is appropriate that they can make decisions on assessment themselves, they would prefer more cooperation and experience sharing with their colleagues.
Keywords: jezik stroke; ocenjevanje znanja; Slovenija; strokovni jezik; tuji jeziki; visoko šolstvo